Análisis de los Estados Financieros de la Cooperativa de Ahorro y Ceédito "Padre Julián Lorente", período 2014 - 2015 - Guarnizo García, Ruth Estefany (2017)
This research was carried out with the objective of carrying out an "ANALYSIS OF THE FINANCIAL STATEMENTS OF THE COOPERATIVE" PADRE JULIÁN LORENTE, "PERIOD 2014-2015"; In order to know its financial and economic study and to make known to the executives of this financial institution, as it has carried out the business work during the periods indicated previously that based on these results take the correctives necessary to improve the situation of the cooperative. For this purpose, a vertical and horizontal analysis of the years 2014 and 2015 was carried out, where the main variations in assets, liabilities, wealth, income and expenses were determined and analyzed. Subsequently we analyzed the liquidity, profitability and constant indebtedness in order to know the degree of management achieved within the business expenses. With the results obtained in this financial analysis was established a report with the most outstanding data of the same, which served to inform the directors of the cooperative the results found and in this way can make correct decisions to improve and therefore Continue to grow in future years. For the development of the same it was necessary to use some methods such as the deductive that allowed to develop the literature review, the inductive method to know the situation of the financial analysis, the analytical used to perform an internal analysis of the entity, using the synthetic method Assertions and generalizations based on the objectives of the investigative work were formulated to finally make the final report, the respective conclusions and recommendations. These methods were complemented with techniques such as direct observation, interview and bibliographic collection methodology that allowed the fulfillment of each of the specific objectives raised. Concluding that in the two study periods a considerable profit is maintained, a situation that allows an adequate operation of its financial operations achieving in the first instance to maintain good solvency and profitability to meet the obligations of the Cooperative